Exploration of Online and Offline Blended Teaching Mode in Undergraduate Nursing Physiology - Cao, Yingdong; Cui, Zhenti; Ren, Pengfei; Qin, Bai (Journal of Educational Research and Policies, 2025)
This paper actively explores the application of the online and offline blended teaching mode in physiology teaching under the background of “Internet+”. In terms of constructing the blended teaching mode, based on the Chaoxing Fanya network platform, course preparation is carried out from several aspects: teaching objects, teaching objectives, and the establishment of a teaching database. In terms of the implementation of the teaching mode, the OBE concept, VR technology, and ideological and political education are organically integrated with professional courses with the help of the network platform, while diversified assessment runs through the entire teaching process, to achieve the purpose of promoting the diversification of teaching methods, improving teaching quality, and cultivating students’ comprehensive learning ability, and has achieved good results.